DNA methylation profiles of ovarian cysts resemble ovarian tissues but not endometrial tissues - Xiaohui Zhang; Xiaojing Zhao; Jiapo Wang; Yifang Zhang; Jinhong Chen (Journal of Ovarian Research, 2024)
Abstract Introduction Endometriosis is a heritable, complex chronic inflammatory disease, for which much of the causal pathogenic mechanism remain unknown.Despite the high prevalence of ovarian chocolate cyst, its origin is still under debate. Methods Prevailing retrograde menstruation model predicts that ectopic endometrial cells migrate and develop into ovarian chocolate cyst. However, other models were also proposed. Genome-wide association studies (GWASs) have proved successful in identifying common genetic variants of moderate effects for various complex diseases. Results A growing body of evidence shows that the remodeling of retrograde endometrial tissues to the ectopic endometriotic lesions involves multiple epigenetic alterations, such as DNA methylation, histone modification, and microRNA expression.Because DNA methylation states exhibit a tissue specific pattern, we profiled the DNA methylation for ovarian cysts and paired eutopic endometrial and ovarian tissues from four patients. Surprisingly, DNA methylation profiles showed the ovarian cysts were closely grouped with normal ovarian but not endometrial tissues. Conclusions These results suggested alterative origin of ovarian cysts or strong epigenetic reprogramming of infiltrating endometrial cells after seeding the ovarian tissue. The data provide contributing to the pathogenesis and pathophysiology of endometriosis.